ARTE RUPESTRE EN LLAPLLAQ’ATA – TAMBOBAMBA: Y SU CONFIGURACIÓN GEOGRÁFICA - Arroyo Abarca, Patricia M. (2017)
In this article we present a hypothesis about rock art and the way in which it is to be understood, and then introduce myself to the process of domestication and grazing of camelids in our area of study, based on the approaches of symbolic and structuralist archeology as well as the Landscape, so that we can assimilate the meaning of material culture and conflicts in the identification of species of camelid in rock art, the colors used and the reuse of this space, at a given time and on the question of why , Preferred these spaces to place their dead and contextualize us with the immediate space in which this society of shepherds of tall camelids developed.